VALIDATION OF SAMYAKVIRIKTALAKSHANA (IDEAL PURIFICATORY SYMPTOMS) WITH RESPECT TO GAMBHEERAVAATARAKTA (CHRONIC ARTHRITIS) - A, *Binitha; Pathak, Malay (International Journal of Ayurveda and Pharma Research, 2017)
Samyaklakshana (ideal symptoms) is the goal in any type of Shodhanachikitsa (purificatory treatment) and the type of Shudhi (purification) will decide the Samsarjanakarma (dietary regimen after purification). Assessment of Samyakviriktalakshana (ideal purificatory symptoms) is a key element in making Virechana (purgation) a Samyakprayoga (ideal practice). An attempt was made to develop and validate a proforma to assess Samyakviriktalakshana (Ideal purificatory symptoms). Samyakviriktalakshana (ideal purificatory symptoms) from all texts were compiled and analyzed for root word, meaning and explanation. One representative Lakshana (symptom) was taken for those conveying the same meaning. Classical references for Vaigikee (urge), Maanikee (volume) and Aantikee (last output) of Shudhi (elimination) were taken and a preliminary proforma was prepared. The clinical study was carried out in 20 participants having Gambheeravatarakta (chronic Arthritis). Conclusions were drawn from statistical work and the pro forma was finalized which determines Shuddhi (purification) based on all four criteria for Samyakviriktalakshana (Ideal purificatory symptoms). Face validity of pro forma was checked in terms of spelling, grammar, layout, readability, transliteration, unambiguousness and overall appearance and was found to be 90%.Content Validity Ratio (CVR) was calculated as 0.44 on 32 experts. The pro forma had good Construct validity. Criterion validity was calculated by comparing the pro forma with the gold standard in 10 observations. The Lakshana found observable at the end of the pilot study, and classical references for Vaigikee (urge), Maanikee (volume) and Aantikee (last output) of Shuddhi (purification) were together taken as gold standard. Criterion validity was found as 80%. Kapha was significant and the confidence interval was moderate. The proforma can be used as a tool to determine Pravara, (finest) Madhyama (moderate) or Avara (least) Shudhi (purification) in a Virechana (purgation).